ENHANCING THE ROLE OF PEACEKEEPING FORCES IN IMPROVING INTERNATIONAL PERCEPTION AND THE DIPLOMATIC IMAGE OF INDONESIA - Sukur Hermanto (Jurnal Academia Praja, 2025)
This research aims to analyse the role of Indonesian peacekeepers in improving international perceptions and the country's diplomatic image. Using a descriptive-analytical method and a qualitative approach, this research explores the contribution of peacekeepers in strengthening Indonesia's diplomatic image in the global arena, as well as assessing the challenges faced in implementing the policy. Data was obtained from interviews with key informants, literature studies, and related documents. The results show that Indonesia is consistently involved in UN peacekeeping missions, which contribute significantly to the country's image enhancement. However, the research also identified a number of obstacles, such as limited resources and international political influence. The research conclusion emphasises the importance of continued efforts in strengthening the role of peacekeeping forces as an instrument of diplomacy to maintain global peace and security, as well as improving coordination between relevant agencies.